2002
DOI: 10.1097/01.asn.0000022011.35035.f3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of Renal Function Equations for Patients with Chronic Kidney Disease and Normal Serum Creatinine Levels

Abstract: Abstract. Accurate renal function measurements are important for the diagnosis and treatment of kidney disease, proper medication dosing, interpretation of possible uremic symptoms, and decision-making regarding when to initiate renal replacement therapy. Because the use of highly accurate filtration markers to measure renal function has traditionally been limited by cumbersome and costly techniques and the involvement of radioactivity (among other factors), renal function is typically estimated by using speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
233
2
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(261 citation statements)
references
References 27 publications
6
233
2
13
Order By: Relevance
“…BMI is known to be an independent risk factor for early mortality after CABG [12]. Other studies [13,14] revealed that the MDRD equation tends to underestimate the actual GFR in patients with chronic kidney disease but normal serum creatinine. This may explain why renal function estimated by the MDRD equation is a less accurate predictor for early mortality when compared with renal function estimated by the Cockcroft-Gault formula.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is known to be an independent risk factor for early mortality after CABG [12]. Other studies [13,14] revealed that the MDRD equation tends to underestimate the actual GFR in patients with chronic kidney disease but normal serum creatinine. This may explain why renal function estimated by the MDRD equation is a less accurate predictor for early mortality when compared with renal function estimated by the Cockcroft-Gault formula.…”
Section: Discussionmentioning
confidence: 99%
“…GFR estimates appear to provide substantial improvements over the measurement of SCr alone in the clinical assessment of kidney function [15]. Several glomerular filtration rate (GFR) prediction equations have been shown to generate sufficiently precise, unbiased and accurate estimates of GFR (eGFR) to be clinically useful for evaluating kidney function in a broad range of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…ADMA 42 was measured by ELISA (DLD, Diagnostika Gmbh, Hamburg, Germany) that we specifically validated in patients with CKD 43 ; intact FGF-23 was measured an ELISA kit (Kainos Laboratories, Tokyo, Japan 44 In this cohort the GFR was measured in all patients by iohexol clearance. 45 In the MMKD cohort, SDMA and L-arginine were also available and were measured as reported elsewhere. 21 …”
Section: Laboratory Measurementsmentioning
confidence: 99%